An Exploratory, Population-Based, Mixed-Methods Program Evaluation of User Satisfaction of Services Provided by a Regional Extension Center (REC) - Tang, D.; Rutala, M.; Ihde, C.; Bills, A.; Mollon, L.; Warholak, T. (Applied Clinical Informatics, 2014)
Objectives: To evaluate user satisfaction among practices receiving services provided by the Arizona Regional Extension Center (REC).Methods: This program evaluation utilized a mixed-methods approach including: 1) a mail-based survey targeting all 489 REC member practices; and 2) a series of telephone-based focus groups using a convenience sample of rural and urban REC member practices. Targeted respondents were key contacts who handle interactions with the REC at each practice. Program evaluators at the University of Arizona and experts at Arizona Health-e Connection (AzHeC) created the questionnaires, focus group script, participant invitation and follow up documents via a collaborative process. Regression and Rasch analyses were used to identify key factors associated with satisfaction with REC and to assess questionnaire validity, respectively.Results: Responses from both the focus groups and survey revealed that most of the respondents were satisfied with the current services, despite the presence of satisfaction gaps between practices of various characteristics: respondents that were clinicians, practices using web-based electronic health record systems (EHRs), and practices that had achieved Stage 1 Meaningful Use had a higher level of satisfaction compared with their respective counterparts. Focus group participants provided suggestions for improving REC services.Conclusions: Most respondents reported being satisfied with REC services. Specialized representatives may be needed for practices at different stages of Meaningful Use to further improve REC satisfaction in order to facilitate more efficient adoption of EHRs.Citation: Tang D, Rutala M, Ihde C, Bills A, Mollon L, Warholak T. An exploratory, population-based, mixedmethods program evaluation of user satisfaction of services provided by a regional extension center (REC). Appl Clin Inf 2014; 5: 1–24 http://dx.doi.org/10.4338/ACI-2013-06-RA-0037
Keywords: Health information technology; user satisfaction; mixed-methods study; regional extension center; meaningful use